Analisis Kebutuhan dan Ketersediaan Air Bersih pada IPA Nelas (PDAM) Perumda Tirta Hidayah Kota Bengkulu Menggunakan Software Stella 10.0.6 - Leo Agustin; Meilani Belladona; Tri Sefrus (MASALIQ, 2026)
Clean water is a basic need for the survival of living beings and constitutes an important aspect of public service provision, particularly for PDAM in improving service levels for the community. The demand for drinking water in a region continues to increase along with population growth, making it necessary to conduct a measurable analysis of clean water needs and availability. This study aimed to analyze clean water needs and availability based on population projections in the service area of IPA Nelas Cahaya Negeri over a 10-year period using Stella 10.0.6 software. The analysis was conducted through population projection modeling to facilitate comparison between clean water needs and community growth over time. The results showed that the population of the IPA Nelas Cahaya Negeri service area in 2033 was projected to reach 338.46 people. Based on this projection, clean water demand was forecast for the domestic and industrial sectors. The calculation results showed that the projected drinking water demand in six regencies in Bengkulu City reached 17,295,424.72 m³/year or 548.434 liters/second. The conclusion of this study emphasizes that projections of clean water needs based on population growth are important as a basis for PDAM service planning so that water availability can be adjusted to the needs of the community and the industrial sector. These findings imply the need to utilize software-based modeling to support more accurate and sustainable clean water distribution planning.